Hydantoins and mercaptoimidazoles: Vibrational spectroscopy as a probe of structure and reactivity in different environments, from the isolated molecule to polymorphs - Fausto, Rui; Brás, E.M.; Nogueira, Bernardo A.; ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2019)
In this chapter, we highlight the power of vibrational spectroscopy as central technique to investigate the structure and reactivity of two relevant families of nitrogen-containing heterocyclic molecules: hydantoins and mercaptoimidazoles. Infrared spectroscopy is used in connection with the matrix isolation technique to investigate the structures of the isolated molecules and their photochemistry, while both infrared and Raman spectroscopies, supplemented by thermodynamics, microscopy, and diffraction techniques, are used to investigate neat condensed phases of the compounds and transitions between these phases. The experimental studies are supported by extensive computational studies, which include several approaches for detailed analysis of the electron density.